Advances in Human Factors in Cybersecurity Proceedings of the AHFE 2017 International Conference on Human Factors in Cybersecurity, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA - Nicholson, Denise; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book reports on the latest research and developments in the field of cybersecurity, placing special emphasis on personal security and new methods for reducing human error and increasing cyber awareness, as well as innovative solutions for increasing the security of advanced Information Technology (IT) infrastructures. It covers a broad range of topics, including methods for human training; novel Cyber-Physical and Process-Control Systems; social, economic, and behavioral aspects of cyberspace; issues concerning the cybersecurity index; security metrics for enterprises; risk evaluation, and many others. Based on the AHFE 2017 International Conference on Human Factors in Cybersecurity, held on July 17-21, 2017, in Los Angeles, California, USA, the book not only presents innovative cybersecurity technologies, but also discusses emerging threats, current gaps in the available systems, and future challenges that may be successfully overcome with the help of human factors research. .
Cybersecurity management through logging analytics -- Adaptive weak secrets for authenticated key exchange -- Internet of things and distributed denial of service mitigation -- Eye tracking graphical passwords -- Understanding and discovering SQL injection vulnerabilities -- Grid framework to address password memorability issues and offline password attacks -- Exploring 3D cybersecurity visualization with the Microsoft HoloLens -- Humans as the strong link in securing the total learning architecture -- Preserving dignity, maintaining security and acting ethically -- Human factors in information security culture: A literature review -- Do you really trust "privacy policy" or "terms of use" agreements without reading them? -- Users' attitudes towards the "going dark" debate -- The use of cloud computing applications in education: Privacy and security concerns. .
Keywords: Computational intelligence; Data protection; User interfaces (Computer systems).; Human-computer interaction; Information technology -- Management; Computer crimes; Computational Intelligence; Data and Information Security; User Interfaces and Human Computer Interaction; Business IT Infrastructure; Cybercrime